2015
DOI: 10.3390/ijms160716158
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Mediated Modulation of Energy Expenditure

Abstract: Thyroid hormone (TH) has diverse effects on mitochondria and energy expenditure (EE), generating great interest and research effort into understanding and harnessing these actions for the amelioration and treatment of metabolic disorders, such as obesity and diabetes. Direct effects on ATP utilization are a result of TH’s actions on metabolic cycles and increased cell membrane ion permeability. However, the majority of TH induced EE is thought to be a result of indirect effects, which, in turn, increase capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 122 publications
(152 reference statements)
1
33
0
2
Order By: Relevance
“…These changes can increase the resting metabolic rate (RMR) and an intense and rapid stimulation of oxygen consumption in experimental models. The pathways involved in the formation and clearance of the T2 are currently unknown [45][46][47]. Previous studies showed that T2 production from the T3 hormone might be less prominent in hypothyroid patients treated with L-T4 [48].…”
Section: Discussionmentioning
confidence: 99%
“…These changes can increase the resting metabolic rate (RMR) and an intense and rapid stimulation of oxygen consumption in experimental models. The pathways involved in the formation and clearance of the T2 are currently unknown [45][46][47]. Previous studies showed that T2 production from the T3 hormone might be less prominent in hypothyroid patients treated with L-T4 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effects of chronic T 4 on metabolic rate, food intake, and thermogenic response are reduced in Ucp1 KO mice, strongly suggesting that metabolic reprogramming of the BAT occurs in these mice. In this connection, TH may facilitate Ucp1-independent thermogenesis by activating futile substrate cycles during glycolysis/gluconeogenesis, lipolysis/lipogenesis, and glycerol-3-phosphate shuttling in brown and beige fat [41,42]. A futile cycle of the arginine/creatine metabolism may also contribute to thermogenesis in the brown and beige adipocytes [43,44].…”
Section: Central and Peripheral Regulation Of Thermogenesismentioning
confidence: 99%
“…The literature suggests that the increase in serum TSH and T3 levels observed in obese individuals occur so as to increase energy expenditure and minimize weight gain [56,57]. This assumption is justified by the role of thyroid hormones in the acceleration of energy metabolism and ATP turnover, especially in the induction of thermogenesis by stimulating the expression and activity of energy uncoupling protein (UCP) [27,57,58]. In this scenario, it is worth mentioning that levels of resting energy expenditure rise in obesity, probably due to the concomitant increase in fat-free mass [59].…”
Section: Energy Expenditurementioning
confidence: 99%